Principles of 137Cs transition from the soil to the plant - V. V. Prorok; L. A. Bulavin; V. A. Ageyev; L. Yu. Melnichenko; A. I. Lypska; V. V. Ostashko (Ядерна фізика та енергетика)
Different kinds of rapidly maturing plants were grown simultaneously at experimental sites under natural conditions at the Chornobyl Exclusion Zone. Content of 137Cs and potassium in the plant and in the corresponding soil solution and content of the soil solution in the soil unit were measured. It was established for the first time, that for all investigated plants and experimental sites 137Cs plant content is approximately proportional to concentration of dissolved 137Cs in the soil. Transition coefficient plant - soil solution is approximately proportional to the content of soil solution per unit of the soil volume.